2019
DOI: 10.1016/j.clnu.2018.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet and knee osteoarthritis outcomes: A longitudinal cohort study

Abstract: Objectives-Mediterranean diet has several beneficial effects on health, but data regarding the association between Mediterranean diet and knee osteoarthritis (OA) are limited mainly to crosssectional studies. We investigated whether higher Mediterranean diet adherence is prospectively associated with lower risk of radiographic OA (ROA), radiographic symptomatic knee OA (SxOA) and pain worsening in North American people at high risk or having knee OA. Methods-Adherence to the Mediterranean diet was evaluated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 28 publications
4
43
0
Order By: Relevance
“…OA progression is significantly related to oxidative stress and ROS [36], suggesting that adequate intake and/or supplementation of Mg can reduce inflammation and oxidative stress, leading to better preservation of knee structures. Third, Mg is particularly present in the Mediterranean diet, rich in vegetables, and, consequently, this can further justify our findings [22,37,38]. Finally, it is widely known that Mg is able to potentiate the effects of vitamin D on the skeletal system, further reinforcing the positive effect of Mg on knee OA [27].…”
Section: Discussionsupporting
confidence: 75%
“…OA progression is significantly related to oxidative stress and ROS [36], suggesting that adequate intake and/or supplementation of Mg can reduce inflammation and oxidative stress, leading to better preservation of knee structures. Third, Mg is particularly present in the Mediterranean diet, rich in vegetables, and, consequently, this can further justify our findings [22,37,38]. Finally, it is widely known that Mg is able to potentiate the effects of vitamin D on the skeletal system, further reinforcing the positive effect of Mg on knee OA [27].…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, these two interventions combined with vitamin D and amino acid supplementation and physical exercise could prevent several sequelae of the aging process including sarcopenia, as shown by several studies in the literature [47][48][49][50][51][52][53]. Finally, it has been demonstrated that there is a strong correlation between the adherence to a Mediterranean diet and a lower risk of OA manifestation, mediated by the well-known anti-inflammatory activity of fibers [54]. Taken together, these findings suggest that a rich in fiber nutritional approach like the Mediterranean diet combined with an adequate intake of micronutrients and physical exercise might be a cornerstone to maintain good health status, particularly in older people.…”
Section: Obesity and Metabolic Syndromementioning
confidence: 99%
“…The Mediterranean diet has been much appreciated for its inclusion of many antioxidant-containing foods. In older adults on a Mediterranean diet, the symptomatic forms of KOA and pain were found to be much lower [ 243 ], while combining a diet that included extra-virgin olive oil with exercise was proved as a beneficial combination for cartilages and joints [ 244 ]. Olive oil is rich in active polyphenols, such as oleuropein, tyrosol, hydroxytyrosol, and oleocanthal, with important antioxidant and anti-inflammatory properties, being an important candidate in the prevention of degenerative changes [ 245 ].…”
Section: The Effects Of Antioxidants In Koamentioning
confidence: 99%